ANALISIS WACANA IDEOLOGI GENDER DALAM FILM KARTINI VERSI 1982 DAN 2017 (STUDI KOMPARATIF) - Jacksen Gunawan; Ngorang Philipus (Jurnal Komunikasi dan Bisnis, 2019)
Feminism is quite influential in popular culture. This can be known from the many products of popular culture (such as film, for example) that the theme of feminism. This study wanted to find out how the construction of feminism in Indonesia films by director Sjuman Djaya (1982) and Hanung Brahmantyo (2017). The object of this research is R.A Kartini (1982) and Kartini (2017). This study is a qualitative descriptive study using a critical discourse analysis method, by adopting the model Sara Mills. This model was adopted because it adjusts the object of research in the form of films. By performing the analysis of two levels, namely the micro level and macro level, obtained results that there is construction of feminism in films that became the object of research, as follows: In the analysis of micro-level, there are some aspects of the center of attention, namely: theme, setting, characters, dialogue, costume, photography, and music. From all of these aspects can be known how the films construct feminism. In the analysis of the macro level, some aspects are used, namely the use of various greeting and a link between social context with the film. Meanwhile, the construction of feminism that is widely available in these films is liberal feminism, which enhances the careers of women's rights, rights of women in sexual terms, and the right of women to determine its future.Keywords : feminism, film, critical discourse analysis, Sara Mills